2003
DOI: 10.1007/s00421-002-0732-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term exposure to intermittent hypoxia results in increased hemoglobin mass, reduced plasma volume, and elevated erythropoietin plasma levels in man

Abstract: While it is well established that highlanders have optimized their oxygen transport system, little is known about the acclimatization of those who move between different altitudes. The purpose of this study was to establish whether the acclimatization to long-term intermittent hypoxic exposure in members of the Chilean Army who frequently move from sea level to 3,550 m altitude is correlated with acute acclimatization or chronic adaptation to hypoxia. A group of officers was exposed intermittently to hypoxia f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
67
3
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 39 publications
9
67
3
1
Order By: Relevance
“…Finally, the duration of the hypoxic periods in the divers probably does not exceed the time necessary for effective erythropoiesis, which is supposed to be at least 80 min of continuous hypoxia (Eckardt et al 1989) or cumulative 240 min of intermittent hypoxia (2.5 min of hypoxia at 10.5% O 2 in N 2 followed by 1.5 min of normoxia, Knaupp et al 1992). Our findings, therefore, reject the hypothesis of elevated tHb-mass providing an additional O 2 -store in trained apnea divers (Heinicke et al 2003). Nevertheless, a lacking long-term effect of apnea training on tHb-mass still needs to be demonstrated in longitudinal studies.…”
Section: Total Haemoglobin Masscontrasting
confidence: 74%
“…Finally, the duration of the hypoxic periods in the divers probably does not exceed the time necessary for effective erythropoiesis, which is supposed to be at least 80 min of continuous hypoxia (Eckardt et al 1989) or cumulative 240 min of intermittent hypoxia (2.5 min of hypoxia at 10.5% O 2 in N 2 followed by 1.5 min of normoxia, Knaupp et al 1992). Our findings, therefore, reject the hypothesis of elevated tHb-mass providing an additional O 2 -store in trained apnea divers (Heinicke et al 2003). Nevertheless, a lacking long-term effect of apnea training on tHb-mass still needs to be demonstrated in longitudinal studies.…”
Section: Total Haemoglobin Masscontrasting
confidence: 74%
“…Remarkably, this finely controlled regulation of Epo gene expression still occurs after decades of weekly exposure of men to intermittent hypoxia. 21 In contrast, in our tg mice an overexpression of human Epo induced excessive erythrocytosis independent of hypoxia and resulted in a 10-to 12-fold elevation of Epo plasma levels. 9 Unexpectedly, the blood pressure was not elevated nor was the cardiac output altered.…”
Section: Introductionmentioning
confidence: 53%
“…Remarkably, this finely controlled regulation of Epo gene expression still occurs after decades of weekly exposure of men to intermittent hypoxia. 21 In contrast, in our tg mice an overexpression of human Epo induced excessive erythrocytosis independent of hypoxia and resulted in a 10-to Supported by grants from the Roche Research Foundation, the EMDO Stiftung, the Stiftung fü r wissenschaftliche Forschung an der Universität Zü rich, the Swiss National Science Foundation (3100A0-100214; M.G. ), by the Forschungsfö rderungsprogramm of the University of Heidelberg (J.V.…”
Section: Introductionmentioning
confidence: 99%
“…106 However, chronic hypoxia is an impractical means to improve brain vascularity, and this procedure also stimulates significant pulmonary hypertension and right ventricular hypertrophy 107 and increased blood viscosity due to increased hematocrit. 108,109 As might be expected, the duration of continuous hypoxia is critical for development of right ventricular hypertrophy. Recently Ma et al 110 reported that more than three weeks at 3000 m altitude was required for rats to develop pulmonary hypertension, a precursor of right ventricular hypertrophy.…”
Section: Intermittent Hypoxic Training (Iht) Improves Cerebrovascularmentioning
confidence: 98%